Bridging pedagogy and technology: A conceptual analysis for software design in educational platforms - Sánchez, Gabriela Pacheco; Escudero-Nahón, Alexandro; Corona, Mauricio Arturo Ibarra; Mandujano, Martín Muñoz (Edelweiss Applied Science and Technology, 2025)
Software design is a difficult concept to define when it comes to educational technology. This is reflected in research related to the design, creation, and development of educational technology platforms. Therefore, it was decided to define the concept of software design using the conceptual cartography method through seven different axes of analysis. As a result, it was possible to identify the different conceptual components, as well as the semantic relationships of software design with other similar concepts in the field of educational technology. The need for standardization in the use and application of techniques and models for the development of educational technology platforms is mentioned. Finally, it is proposed that future work include the development of a software tool that allows the creation of platforms considering both technical and pedagogical aspects.